2013
DOI: 10.2320/jinstmet.jc201314
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Electroless Ni-P Plating on the Mechanical Properties of an Al-1.2%Si Alloy

Abstract: In this study, the effect of electroless Ni P plating on the mechanical properties of an Al 1.2Si alloy was investigated. As results, the following points were clarified. (1) Fatigue strength of the specimen subjected to zincate treatment only after furnace cooling treatment was almost the same as the furnace cooling only. (2) Fatigue strength of the specimen subjected to Ni P plating after furnace cooling treatment, was reduced overall, except for high stress region, rather than one of non processing ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…7) However, in the electroless NiP plating of AlSi and Al CuMg aluminum alloys containing micron-sized precipitates, it has been observed that the hydrogen absorbed in the material during plating adversely affects the fatigue strength. 8,9) Because A7075 aluminum alloy exhibits high hydrogen embrittlement sensitivity, 10) there is a concern that the hydrogen absorbed in this material by electroless NiP plating may adversely affect its fatigue strength.…”
Section: Introductionmentioning
confidence: 99%
“…7) However, in the electroless NiP plating of AlSi and Al CuMg aluminum alloys containing micron-sized precipitates, it has been observed that the hydrogen absorbed in the material during plating adversely affects the fatigue strength. 8,9) Because A7075 aluminum alloy exhibits high hydrogen embrittlement sensitivity, 10) there is a concern that the hydrogen absorbed in this material by electroless NiP plating may adversely affect its fatigue strength.…”
Section: Introductionmentioning
confidence: 99%